Evolutionary Diversity of Prophage DNA in Klebsiella pneumoniae Chromosomes - Wang, Fengling; Wang, Dongguo; Hou, Wei; Jin, Qian; Feng, Jiao; Zhou, Dongsheng (Frontiers in Microbiology, 2019)
Mobile gene elements play an important role in the continuous evolution of the prophage DNA of bacteria, promoting the emergence of new gene structures. This study explored the evolution of four strains of Klebsiella pneumoniae harboring prophages, 19051, 721005, 911021, and 675920, and 16 genomes of K. pneumoniae from GenBank. The results revealed a wide range of genetic variation in the prophage DNA inserted into the sap sites of K. pneumoniae chromosomes. From analysis and comparison of the sequences of the 20 prophage DNAs determined from the four strains and the 16 GenBank genomes of K. pneumoniae using high-throughput sequencing and antimicrobial susceptibility tests, we identified a novel transposon, Tn6556. We also identified at least nine large genetic structures with massive genetic acquisitions or losses and five hotspot sites showing a tendency to undergo insertion of gene elements such as IS1T, IS1R, IS26, ISKpn26, ISKpn28, Tn6556, MDR and In27-related regions as variable regions; however, the only highly conserved core genes were int and umuCD among the 20 prophage DNAs. These findings provide important insights into the evolutionary diversity of bacteriophage DNA contained in K. pneumoniae.